1993
DOI: 10.1111/j.1365-2249.1993.tb08198.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of TCR γδ+ T cells in tumour-infiltrating lymphocytes (TIL) of human pancreatic cancer

Abstract: In six patients with advanced pancreatic carcinoma, TIL and tumour-draining lymphocytes (TDL) were isolated from primary pancreatic tumour and regional lymph nodes. In comparison with TDL and peripheral blood lymphocytes (PBL), TIL contained a comparatively higher percentage of TCR gamma delta+ cells, although they were still a small fraction. By 2 weeks culture with rIL-2 and immobilized OKT-3 antibody, the TCR gamma delta+ cells in TIL were preferentially expanded at the early culture periods, although it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Interestingly, the A3D8 anti CD44 antibody that did not block HA binding to CD44, inhibited cell migration in our model and in other models (12,51), probably by preventing CD44 conformation changes induced by HA binding. However, in other systems it did not affect migration (53). Other pathways involving VCAM and ICAM proteins could control the migratory capability of AoSMCs.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, the A3D8 anti CD44 antibody that did not block HA binding to CD44, inhibited cell migration in our model and in other models (12,51), probably by preventing CD44 conformation changes induced by HA binding. However, in other systems it did not affect migration (53). Other pathways involving VCAM and ICAM proteins could control the migratory capability of AoSMCs.…”
Section: Discussionmentioning
confidence: 83%
“…Preferential expansion and antitumor responses of subsets of γ/δ TILs have been found in many kinds of cancer, including colorectal cancer [4, 5], lung adenocarcinoma [6, 7]and pancreatic cancer [8]. Such γ/δ T cells demonstrated a non–MHC–restricted recognition and cytolytic activity to autologous/allogeneic tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the tumor ligands recognized by these subsets are likely to be distinct. Indeed, although V␦1 T cells derived from TIL kill a wide array of solid tumors (7)(8)(9)(10)(11), V␥9V␦2 T cells preferentially kill hemopoietic tumor cell lines, such as myeloma, lymphoma, and erythroleukemia (12)(13)(14)(15). However, more recent studies reported recognition of some melanoma and renal carcinoma cell lines by V␥9V␦2 T cells and killing of autologous metastatic renal carcinoma cells (RCC) by autologous PBL-derived V␥9V␦2 T cell lines (16 -18).…”
mentioning
confidence: 99%